Identification and characterization of putative targets of VEGETATIVE1/FULc, a key regulator of development of the compound inflorescence in pea and related legumes - Serra-Picó, Marcos; Hecht, Valérie; Weller, James L.; Benlloch, Reyes; Madueño, Francisco (Frontiers in Plant Science, 2022)
Inflorescence architecture contributes to essential plant traits. It determines plant shape, contributing to morphological diversity, and also determines the position and number of flowers and fruits produced by the plant, thus influencing seed yield. Most legumes have compound inflorescences, where flowers are produced in secondary inflorescences (I2), formed at the flanks of the main primary inflorescence (I1), in contrast to simple inflorescences of plants like Arabidopsis, in which flowers are directly formed on the I1. The pea VEGETATIVE1/FULc (VEG1) gene, and its homologs in other legumes, specify the formation of the I2 meristem, a function apparently restricted to legumes. To understand the control of I2 development, it is important to identify the genes working downstream of VEG1. In this study, we adopted a novel strategy to identify genes expressed in the I2 meristem, as potential regulatory targets of VEG1. To identify pea I2-meristem genes, we compared the transcriptomes of inflorescence apices from wild-type and mutants affected in I2 development, such as proliferating inflorescence meristems (pim, with more I2 meristems), and veg1 and vegetative2 (both without I2 meristems). Analysis of the differentially expressed genes using Arabidopsis genome databases combined with RT-qPCR expression analysis in pea allowed the selection of genes expressed in the pea inflorescence apex. In situ hybridization of four of these genes showed that all four genes are expressed in the I2 meristem, proving our approach to identify I2-meristem genes was successful. Finally, analysis by VIGS (virus-induced gene silencing) in pea identified one gene, PsDAO1, whose silencing leads to small plants, and another gene, PsHUP54, whose silencing leads to plants with very large stubs, meaning that this gene controls the activity of the I2 meristem. PsHUP54-VIGS plants are also large and, more importantly, produce large pods with almost double the seeds as the control. Our study shows a new useful strategy to isolate I2-meristem genes and identifies a novel gene, PsHUP54, which seems to be a promising tool to improve yield in pea and in other legumes.